2014
DOI: 10.1097/prs.0000000000000672
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen, Nonsteroidal Anti-Inflammatory Drugs, and Cyclooxygenase-2 Selective Inhibitors

Abstract: Plastic and cosmetic surgery is often performed as an ambulatory procedure, and pain is often mild to moderate. Good pain relief is central to patient comfort and satisfaction. Analgesics used should ensure rapid onset and adequate pain relief lasting a sufficiently long duration with minimal or no side effects. Acetaminophen is well tolerated by patients, efficacious, and associated with only minor side effects, when used in the minimal effective doses. Nonsteroidal anti-inflammatory drugs (NSAIDs) are more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 41 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…In this context, consideration of non-opioid pain medications during the perioperative period is critical. Acetaminophen results in improved analgesia when taken in conjunction with narcotics and simultaneously decreases opioid consumption [17] and should be prescribed after plastic surgery procedures [42]. Multiple meta-analyses studying gabapentin and pregabalin concluded that both drugs improve pain control post-operatively and decrease narcotic use with very acceptable risk-benefit ratios [43].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, consideration of non-opioid pain medications during the perioperative period is critical. Acetaminophen results in improved analgesia when taken in conjunction with narcotics and simultaneously decreases opioid consumption [17] and should be prescribed after plastic surgery procedures [42]. Multiple meta-analyses studying gabapentin and pregabalin concluded that both drugs improve pain control post-operatively and decrease narcotic use with very acceptable risk-benefit ratios [43].…”
Section: Discussionmentioning
confidence: 99%
“…48 All patients without contraindications should receive regular acetaminophen postoperatively. 49 Ibuprofen has been shown to have equivalent pain control outcomes to acetaminophen/codeine in oncologic breast surgery. 50 Similarly, 68.3 percent of liposuction patients in a large series had sufficient pain control without use of opioids.…”
Section: Recommendationsmentioning
confidence: 99%
“…50 Similarly, 68.3 percent of liposuction patients in a large series had sufficient pain control without use of opioids. 51 COX-2 inhibitors such as celecoxib are associated with a lower bleeding risk than nonsteroidal antiinflammatory drugs 49 and have been shown to reduce opioid requirements in plastic surgery patients postoperatively, 52 although they should be avoided in patients with ischemic heart disease. Preoperative injection of the surgical incision site with local anesthetic has been shown to decrease opioid requirements in breast reduction.…”
Section: Recommendationsmentioning
confidence: 99%
“… 36 NSAIDs are more effective than other adjunct oral medications with lower numbers needed to treat. 37 …”
Section: Nsaids and Cox-2-specific Inhibitorsmentioning
confidence: 99%
“… 39 However, there remains no high-level evidence to support their contraindication in most plastic surgical patients, and several large reviews have concluded that there is no difference in hematoma rates associated with NSAID use. 37 , 40 – 42 A recent meta-analysis reviewing 15 studies with 3064 cumulative patients demonstrated no increase in hematoma with the use of several types of NSAIDs across a variety of plastic surgical procedures including breast surgery. 43 In breast and body contouring procedures, Kelley et al reviewed 106,279 patients; among these, 4,924 (4.6%) patients received postoperative ketorolac.…”
Section: Nsaids and Cox-2-specific Inhibitorsmentioning
confidence: 99%